2015
DOI: 10.1155/2015/868109
|View full text |Cite
|
Sign up to set email alerts
|

XPS, FTIR, EDX, and XRD Analysis of Al2O3Scales Grown on PM2000 Alloy

Abstract: This work is an original example to compare the results obtained after calcination of Al2O3hydroxides and oxidation of alumino-formers alloys. FTIR and XPS signatures were obtained for various oxidation temperatures and compared with those known from the literature about calcination of Al2O3precursors. The aim of this work is to evaluate the use of IR spectroscopy and XPS analysis to probe the structural varieties of Al2O3. For this objective, a study of the PM2000 oxidation at various temperatures was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(93 citation statements)
references
References 41 publications
5
87
0
1
Order By: Relevance
“…The composition is the same as the foil, with the percentage of Al exceeding the percentage of oxygen, as seen from the inset of Fig 4B in case of the Al particles too. This confirms that the material is still aluminium and has not transformed to aluminium oxide (in which case the oxygen percentage will be higher than that of Al) 20 .…”
Section: Resultssupporting
confidence: 57%
“…The composition is the same as the foil, with the percentage of Al exceeding the percentage of oxygen, as seen from the inset of Fig 4B in case of the Al particles too. This confirms that the material is still aluminium and has not transformed to aluminium oxide (in which case the oxygen percentage will be higher than that of Al) 20 .…”
Section: Resultssupporting
confidence: 57%
“…The C 1 s high-resolution XPS spectrum of eroded APIX100 steel at 80 m/s and 90 • impact angle indicates two peaks of carbon at different binding energies, which also belongs to the target API X100 steel material. However, the peak at 74.1 eV binding energy can be associated to the presence of aluminium on the API X100 steel surface [48]. It can be concluded that Fe and C found on the eroded API X100 steel surface belong to the target steel specimens, while the aluminium found on the eroded API X100 steel surface is of the erodent solid particles.…”
Section: Xps Resultsmentioning
confidence: 92%
“…It has also been reported [50,51] that metal removal under low impact angle and high speed conditions occurs by the low-angle metal cutting process as observed in this study (Figure 9a-c). On repeated contact, subsurface plastic strain is built up with increasing cycles resulting in formation of pits on the surfaces, as seen when the test was conducted However, the peak at 74.1 eV binding energy can be associated to the presence of aluminium on the API X100 steel surface [48]. It can be concluded that Fe and C found on the eroded API X100 steel surface belong to the target steel specimens, while the aluminium found on the eroded API X100 steel surface is of the erodent solid particles.…”
Section: Discussionmentioning
confidence: 96%
“…The band at 700 cm −1 also corresponded to the FeO bonds While the bands at 595 and 656 correspond to Al O stretching mode, the band at 715 cm −1 was assigned to the symmetric bending of AlOH …”
Section: Resultsmentioning
confidence: 98%